Literatur Review : Terapy Musik Terhadap Hipertensi Kehamilan - Ahmaniyah Ahmaniyah; Ratna Indriyani (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
Abstract Hypertension in pregnancy is a complication of pregnancy in general, which affects 2% of pregnant women in the world. And is a cause of death of pregnant women in the world, the handling of hypertension is done conventionally, namely hypertension-lowering drugs, but this conventional treatment has many obstacles because it is related to pregnant women who will certainly be related because it is related to pregnant women who will definitely be related to the fetus. Objective: to analyze which music therapy is most effective in reducing blood pressure in pregnant women who have hypertension. Method: This research was reviewed from an electronic database including Science Direct, Pubmed, Google Scholar and other related websites. With the keywords "hypertension, music, pregnancy". A total of 4 of the 5,840 publication ranges from 2015 to December 2019, which discussed music therapy in pregnant women with hypertension and were presented in English, were included in this review. In addition, relevant textbook chapters and guidelines are examined to capture further information or additional reports not identified in the electronic search. Results: from the analysis of many studies showed that music therapy with an average duration of 30 minutes for 1 month showed significant results in reducing hypertension in pregnant women. Conclusion: Music therapy is a significant effort combined with conventional therapy for reducing systolic and diastolic pressure in hypertensive pregnant women. Key word: Pregnancy, Music, Hypertension